2022
DOI: 10.53703/001c.36755
|View full text |Cite
|
Sign up to set email alerts
|

When ‘Good Enough’ Is Not Enough: The Role of Maximizing or Satisficing Decision-Making Styles, Innovation Behavior, and Entrepreneurial Alertness in the Pursuit of New Business Opportunities

Abstract: This paper investigates whether an individual’s tendency to maximize when making decisions influences their entrepreneurial intentions, innovation behavior, entrepreneurial alertness, and opportunity evaluation. It is predicted that maximizers will have greater entrepreneurial intentions. Underlying this process, it is predicted that maximizers will report greater innovation behavior and entrepreneurial alertness. Using data from a survey of 253 working professionals in the U.S., hypotheses are tested using mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 117 publications
0
4
0
Order By: Relevance
“…This observed relationship might be explained by the fact that decision-makers who can handle their emotions also tend to deal easily with complex decisions by focusing their attention only on the relevant information and reducing the overwhelm and fatigue caused by challenging decisions such as routinary clinical decisions (Soltwisch, 2015). Coherently, emotionally intelligent individuals may also find less decision difficulty, regret, self-blame, and more adaptation due to their capacity to weigh alternatives and see other viewpoints (Schwartz et al, 2002; Soltwisch & Krahnke, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This observed relationship might be explained by the fact that decision-makers who can handle their emotions also tend to deal easily with complex decisions by focusing their attention only on the relevant information and reducing the overwhelm and fatigue caused by challenging decisions such as routinary clinical decisions (Soltwisch, 2015). Coherently, emotionally intelligent individuals may also find less decision difficulty, regret, self-blame, and more adaptation due to their capacity to weigh alternatives and see other viewpoints (Schwartz et al, 2002; Soltwisch & Krahnke, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been found that maximizers in the U.S. have a more innovative mindset and are more entrepreneurially orientated, which makes them more likely to see entrepreneurship as a viable career path ( Soltwisch et al, 2022 ). It makes sense that entrepreneurship may be a viable means for achieving better results for those who maximize, especially in the U.S., where the economic environment may favor those who take steps to create a better future for themselves.…”
Section: Model Construction and Theoretical Hypothesismentioning
confidence: 99%
“…The goals of social entrepreneurs often require considerable effort, and it is important for entrepreneurs to build support for others to help reach the venture’s goals. Maximizers are more innovative and identify additional opportunities for new businesses in their environment ( Soltwisch et al, 2022 ). They persistently seek out additional information and options to find better solutions.…”
Section: Model Construction and Theoretical Hypothesismentioning
confidence: 99%
See 1 more Smart Citation